JURIDICAL REVIEW OF CUSTOMER SATISFACTION LINKED TO CONSUMER PROTECTION LAW IN PHARMACY MANAGEMENT - Citra, Helfira; Wahyuni, Sry; Rafasya, Raudhatul (LPPM STIH Putri Maharaja, 2023)
Service quality is an essential factor that can provide satisfaction for customers. Nowadays, humans start by filling current interests into fundamental human interests. The form of interest is the interest in health services (pharmaceuticals). Health is one of the necessities of life, and as is often said, health is essential to support daily life, and health is indeed expensive. When you are sick, your everyday life is affected, and you may not be able to walk well. People realise that health is essential because they cannot live decent lives if their health needs are unmet. Referring to Consumer Protection Law No. 8 of 1999, consumers have several rights, including comfort, security and safety in consuming products and services and choosing them according to the exchange rate and conditions according to the agreement. This research aims to develop a consensus between pharmacy managers and suppliers regarding customer satisfaction. In this research, we will use a sociological (empirical) legal approach, namely examining legal guidelines from the point of view of their application. Meanwhile, the research category carried out in this research is analytical descriptive. This research obtains a complete description of the forms of agreements or agreements between pharmacy managers and suppliers to achieve consumer protection; this consumer protection is based on benefits, justice, balance, consumer security and safety, and legal certainty. In this case, the form of agreement in this paper is using an obligatory agreement, namely a consensual agreement contained in Book 3 of the Civil Code, and a consensual agreement, namely an agreement that is binding after both parties have reached an agreement.